Analisis Pertumbuhan Ekonomi Kota Dan Kabupaten Pada Kawasan Metropolitan Banjarbakula - Muhammad Yospi; Ryan Juminta Anward (PPJP ULM, 2020)
This research is a quantitative descriptive study by processing and analyzingeconomic growth data, location quotient values, shift-share, and typology Klassen in theBanjarbakula Region. The type of data used for analysis is secondary data in the form oftime series between 2014-2018 obtained from BPS in each Banjarbakula region.The results showed that the LQ value for each region of the Banjarbakula regionwas different and had another leading sector. This makes the Banjarbakula Region haveadvantages in each sector, which is divided into each area. Economic growth in the cityand district of Banjarbakula is increasing since the 2015-2018. The total GRDP of theBanjarbakula Region as a whole also experienced an increase of Rp6,369,560,000,000.21. The growth of each sector in Banjarbakula is also in threedifferent quadrants, and the most dominant is in the fast-growing industry.